Visible light degradation of tetracycline by hierarchical nanoflower structured fluorine-doped Bi2WO6. (15th March 2022) - Chen, Yulin; Zhang, Feifei; Guan, Shangyi; Shi, Wei; Wang, Xiaoyu; Huang, Chenting; Chen, Qiang
Abstract: Fluorine-doped Bi2 WO6 samples were synthesized by a simple one-step hydrothermal method. The structure and the photocatalytic performance of the as-prepared catalysts were systematically investigated using a variety of characterization methods. Meanwhile, the possible mechanism of photodegradation was discussed. Combined with the analysis of X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and energy dispersive spectrometry (EDS), it was proved that fluorine has been successfully doped into the Bi2 WO6 (BWO) crystal lattice, and its crystal structure remains orthorhombic. With the doping of fluorine, the morphology of Bi2 WO6 changed from a two-dimensional ultrathin nanosheet to a hierarchical nanoflower microstructure. This hierarchical nanoflower structure as well as the strong electronegativity of fluorine are the reasons for the enhanced degradation of pollutants (tetracycline, TC for short). For the optimum composition labeled as F-BWO4, the apparent rate constant (k) of degrading TC is about 4.5 times that of Bi2 WO6, and the degradation rate decreased by only 10% over four cycle degradation experiments. Graphical abstract: Image 1 Highlights: The changes of fluorine doping on the morphology and structure of the Bi2 WO6 were explored. For the optimum composition labeled as F-BWO4, the apparent rate constant (k) of degrading tetracycline is about 4.5 times that of Bi2 WO6 . The photocatalytic performance and related mechanism of the photocatalyst were studied. The possible degradation pathways and intermediate products produced in the process of photocatalyst degradation of TC were analyzed.